Perahu Ketinting Bagi Masyarakat Nelayan di Kabupaten Banyuwangi: Pengabdian Masyarakat oleh Akademi Penerbang Indonesia Banyuwangi - Ahmad Hariri; Ridho Rinaldi (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2022)
The fishing community is one of the community groups that need attention and assistance. This community service activity is carried out by the Banyuwangi Indonesian Aviation Academy (APIB) with the aim of providing assistance to the fishing community. The activity partners are the community in Kedungasri village, Muncar sub-district and Wringinputih village, Tegaldlimo sub-district. The assistance provided is 1 unit of ketinting boat for each partner. The handover of aid is given directly by signing the Handover Sertificate of Grants with the Village Heads of the two partners. The handover activity was also attended by the Head of the District. This activity is a form of APIB's contribution to the surrounding community.